Ethnic Dynamics in North Sumatra - Herlina Jasa Putri Harahap (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2021)
The mention of ethnic group in the North Sumatra was constructed by outsiders. The concepts of "Batak" and "Malay" are given by the outside world as labels. When used to refer to the population combined with this unity, these labels become evasive identities. Architecture is based on natural, cultural and religious fortresses and the social changes surrounding them. Although unification was rejected, it still appeared in various social science literature. This fact had an impact on the truth and error that was considered essential, especially in the second decade of the third millennium. Recent studies and various empirical evidence confirm that mentioning the ethnic groups in North Sumatra and stigmatizing them is an external construction, avoiding identity, and it is now widely rejected.